Співпраця суб’єктів федерації Бельгії на транскордонному, транснаціональному та міжрегіональному рівнях - Мишляєв, Т. Ю.; Myshlyayev, T. Yu. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The features of the Belgian cross-border, transnational and interregional cooperation are examined. The main aspects of Belgian cooperation in the framework of Interreg IV programme are investigated. The participatiom of the Belgian federation subjects as the sub-national actors in the Interreg IV programme within the euroregions is analyzed.
The cooperation of the Belgian federation subjects on the cross-border, trans-national and inter-regional levels
Т.Ю. Мишляєв, аспірант Східноєвропейського національного університету імені Лесі Українки Науковий керівник – д. політ. н., проф. кафедри міжнародної інформації СНУ ім. Лесі Українки Тихомирова Є.Б. (Україна, м. Луцьк)
Keywords: Interreg IV; sub-national actor; euroregio; the cross-border region